Tree and shrub structure composition and diversity in three forest management conditions in Ixtlan de Juarez, Oaxaca - Vásquez-Cortez, Vicente Florencio; Clark-Tapia, Ricardo; Manzano-Méndez, Filemón; González-Adame, Gabriel; Aguirre-Hidalgo, Victor (Instituto de Ecología, A.C., 2018)
Forest activities play a critical role in the natural dynamics of this ecosystem. The aim of this work was to evaluate the effect in structure composition and forest and shrub diversity of the forest management practices applied in Ixtlán de Juárez, Oaxaca. We established 15 sampling areas distributed among three silvicultural treatments: not harvested strips (FNA), edges (B), and harvested strips (FA) established in a strip clearcut timber harvesting forest. Changes in structure, floristic composition and diversity of trees and shrubs strata are described. Twenty-seven species and nine botanical families were identified, being the most frequent Quercus crassifolia Humb & Bonpl., Pinus pseudostrobus Lindl. and Quercus laurina Humb. & Bonpl. Accumulation species-area curves were estimated, showing that the FNA condition had the highest number of species. Through the importance value index (IVI) and forest value index (IVF) it was found that structural value varied for each species, size class (stems, stalks and saplings), and condition (FNA, B and F). Higher values on IVI and IVF were consistently obtained by the three previously mentioned species in the three conditions. However, stems represented the dominant structure in FNA and B while stalks and saplings were dominant in FA. According to diversity indices, richness was low, but evenness was high in the three conditions (FNA, B, FA). Also, dominance was high in FA. B and FA condition were the most similar between them. We concluded that during the period analyzed the silvicultural practices promote an even-aged forest. However, this pattern is less intense because of FNA presence which could limit arboreal and shrub diversity loss.